IDENTIFICATION OF EFFECTIVE TEACHING METHODS USING IN MATHEMATICS PRE-SERVICETEACHERS TRAINING - DOFKOVÁ, Radka; BÁRTEK, Květoslav; FAČEVICOVÁ, Kamila; HODAŇOVÁ, Jitka; LAITOCHOVÁ, Jitka; NOCAR, David; UHLÍŘOVÁ, Martina; ZDRÁHAL, Tomáš (Trends in education, 2017)
Thegoalofthispaperis to identifyteachingmethodswhich are using in pre-serviceteacherstraining. Wewouldlike tochosethoseinnovativeapproacheswhichengagedwithdeveloping and enhancingpre-serviceteachers' mathematicalsubjectknowledge.Wewouldlike to followexperienceswhichmayenrichourapproach to teachereducationwithnewideas. Weaimataddressingthedifferentopportunities and challengeswemeet in teachermathematicseducation. The second part presentstheresultsfromthesurvey, whichwas done atthe department ofmathematics. Teachersofallmathematicssubjectswereinvolved to obtainthebest model ofteachingmethods.Wetakeitas theopportunity to make reflectionofourwork and to improvemathematicspre-serviceteacherstraining.
Keywords: teacher; mathematics; teaching method; pre-service teacher training